Production and applications of engineered viral capsids - Glasgow, Jeff; Tullman-Ercek, Danielle (Applied microbiology and biotechnology, 2014)
As biological agents, viruses come in an astounding range of sizes, with varied shapes and surface morphologies. The structures of viral capsids are generally assemblies of hundreds of copies of one or a few proteins which can be harnessed for use in a wide variety of applications in biotechnology, nanotechnology, and medicine. Despite their complexity, many capsid types form as homogenous populations of precise geometrical assemblies. This is important in both medicine, where well-defined therapeutics are critical for drug performance and federal approval, and nanotechnology, where precise placement affects the properties of the desired material. Here we review the production of viruses and virus-like particles with methods for selecting and manipulating the size, surface chemistry, assembly state, and interior cargo of capsid. We then discuss many of the applications used in research today and the potential commercial and therapeutic products from engineered viral capsids.